Strategi Pengendalian Konversi Lahan Sawah untuk Mempertahankan Swasembada Pangan di Kabupaten Toba: Strategies to Control Paddy Field Conversion for Mantaining Food Sufficiency in Toba Regency - Tugma Jaya Manalu; Dyah Retno Panuju; Untung Sudadi (Jurnal Ilmu Tanah dan Lingkungan, 2022)
The food crisis is an important issue faced by many countries, including Indonesia. Paddy field conversion caused decreasing rice production in many regions, one of which is in Toba Regency. Paddy field conversion should be controlled strategically to maintain the existence of the field for food production. This study aims: 1) to identify the conversion, availability, and rice needs 2) to identify the strengths, weaknesses, opportunities, and threats (SWOT factor) affecting paddy field conversion, 3) to generate strategies that control paddy field conversion. The SWOT factors were identified through descriptive methods, literature studies, and interviews. The strategies were constructed using a hybrid Analytical Hierarchy Process (AHP) and SWOT method. The results showed that rice availability decreased by -7,030 and demand increased by 4,001 tons between 2010 and 2020 due to paddy field conversion by 3,529 ha and increasing population. The main strength to be considered for controlling paddy field conversion is managing rice land, while the main weakness that might hinder the strategy is the low level of farmer education. Moreover, the main opportunity is supporting accessibility, and the main threat was regulation concerning sustainable agricultural land. The essential strategies to control paddy field conversion in Toba Regency include Land Protection Regulation, the subsidy of production input to farmers, and use of the local government budget to build agricultural infrastructure.